Geochemical and ecological assessment of some heavy metals in the soil around the lead and zinc mine in northwestern of Iran - Sadegh Hosseinniaee (Tehran University of Medical Sciences, 2021)
Background and Objective: Today, soil and water pollution with heavy metals is one of the major challenges around the world. The aim of this study is to investigate the contamination of soils around a lead and zinc mine. Materials and Methods: In the summer of 2019, 100 soil samples were taken from the mine vicinity and the characteristics of texture, acidity, salinity, calcium carbonate, organic matter and heavy metals chromium, cobalt, zinc, lead and cadmium were measured. Pollution indices including pollution factor (PI), enrichment coefficient (EF), geoaccumulation (Igeo), toxicity probability (MERMQ), contamination load (PLI), background enrichment (PIN), pollution security (CSI) and Nemerow index (PINemerow) ) Were calculated. Correlation between soil variables and determination of metal origin were determined using Pearson correlation and principal component analysis (PCA) analysis. Results: The average concentrations of chromium, cobalt, zinc, lead and cadmium were obtained as 92, 21.33, 453.98, 351.24 and 4.28 mg/kg, respectively. The metals pollution evaluated based on PI, EF and Igeo indices were moderate for chromium and cobalt, considerable for zinc and significant for lead and cadmium. The results of MERMQ, PLI, PIN, CSI and PINemerow indices showed high soil contamination with heavy metals. According to the PCA test, the elements lead, zinc and cadmium are in a group with high correlation with each other that are of anthropogenic origin. Chromium and cobalt with a correlation of 88% also showed the same geological origin. Conclusion: mining activities should be done with more caution and measures should be taken to reduce pollution.